Selection of Environmental Covariates for Classifier Training Applied in Digital Soil Mapping - Alcinei Ribeiro Campos; Elvio Giasson; José Janderson Ferreira Costa; Israel Rosa Machado; Elisângela Benedet da Silva; Benito Roberto Bonfatti (Revista Brasileira de Ciência do Solo, 2018)
ABSTRACT A large number of predictor variables can be used in digital soil mapping; however, the presence of irrelevant covariables may compromise the prediction of soil types. Thus, algorithms can be applied to select the most relevant predictors. This study aimed to compare three covariable selection systems (two filter algorithms and one wrapper algorithm) and assess their impacts on the predictive model. The study area was the Lajeado River Watershed in the state of Rio Grande do Sul, Brazil. We used forty predictor covariables, derived from a digital elevation model with 30 m resolution, in which the three selection models were applied and separated into subsets. These subsets were used to assess performance by applying four prediction algorithms. The wrapper method obtained the best performance values for the predictive model in all the algorithms evaluated. The three selection methods applied reduced the number of covariables in the predictive models by 70 % and enabled prediction of the 14 soil mapping units.